Virulence and immunogenicity of genetically defined human and porcine isolates of M. avium subsp. hominissuis in an experimental mouse infection. - Nicolas Bruffaerts; Christelle Vluggen; Virginie Roupie; Lucille Duytschaever; Christophe Van den Poel; Joseph Denoël; Ruddy Wattiez; Jean-Jacques Letesson; David Fretin; Leen Rigouts; Ophélie Chapeira; Vanessa Mathys; et al. (PLoS ONE)
Mycobacterium avium subsp. hominissuis (Mah) represents a health concern for humans and to a lesser extent for pigs, but its zoonotic potential remains elusive. Using multispacer sequence typing (MST) we previously identified 49 different genotypes of Mah among Belgian clinical and porcine isolates, with 5 MSTs shared by both hosts. Using experimental intranasal infection of BALB/c mice, we compared the virulence and immunogenicity of porcine and clinical human isolates with shared genotype or with a genotype only found in humans or pigs. Bacterial replication was monitored for 20 weeks in lungs, spleen and liver and mycobacteria specific spleen cell IFN-γ, IL-10 and IL-17 production as well as serum antibody responses were analyzed. Isolates varied in virulence, with human and porcine isolates sharing MST22 genotype showing a thousand fold higher bacterial replication in lungs and more dissemination to spleen and liver than the human and porcine MST91 isolates. Virulent MST22 type was also associated with progressive suppression of IFN-γ and IL-17 responses, and increased IL-10 production. Whole genome sequencing of the two virulent isolates with MST22 genotype and two avirulent isolates of genotype MST91 and comparison with two well-studied M. avium subsp. hominissuis reference strains i.e. Mah 104 and Mah TH135, identified in the two MST22 isolates nine specific virulence factors of the mammalian cell entry family, that were identical with Mah 104 strain. Despite the obvious limitations of the mouse model, a striking link of virulence and identity at the genome level of porcine and human isolates with the same multisequence type, for which no correlation of place of residence (humans) or farm of origin (pigs) was observed, seems to point to the existence in the environment of certain genotypes of Mah which may be more infectious both for humans and pigs than other genotypes.